2016
DOI: 10.1371/journal.pone.0166539
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in HIV-Infected Alcohol and Drug Users in St. Petersburg, Russia

Abstract: In Russia, up to half of premature deaths are attributed to hazardous drinking. The respective roles of alcohol and drug use in premature death among people with HIV in Russia have not been described. Criminalization and stigmatization of substance use in Russia may also contribute to mortality. We explored whether alcohol, drug use and risk environment factors are associated with short-term mortality in HIV-infected Russians who use substances. Secondary analyses were conducted using prospective data collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…With that said, under-reporting of mortality among those LTFU could still be an issue. In Russia and in the Veterans Aging Cohort Study, hazardous alcohol use increased overall mortality among HIV-infected substance users [ 36 , 37 ], and substance users lost to follow up may have a higher chance of being dead than non-users. There was insufficient follow-up in our study to investigate any association between substance use and mortality; additional studies with longer follow up periods are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…With that said, under-reporting of mortality among those LTFU could still be an issue. In Russia and in the Veterans Aging Cohort Study, hazardous alcohol use increased overall mortality among HIV-infected substance users [ 36 , 37 ], and substance users lost to follow up may have a higher chance of being dead than non-users. There was insufficient follow-up in our study to investigate any association between substance use and mortality; additional studies with longer follow up periods are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…For example, alcohol consumption has been linked with risky sexual behaviors that may increase the likelihood of HIV transmission [15][16][17]. Also, people living with HIV who use alcohol are approximately 50%-60% less likely to be adherent to antiretroviral therapy than abstainers [18], and heavy drinking is related to increased risk of detectable viral load, impaired liver function, and death [19][20][21]. Thus, a better understanding of the link between HIV-related stigma and alcohol use is necessary to curb their negative impact on the health and well-being of people living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Another Russian study, among PLWH, reported that hospitalized, alcohol-dependent patients consumed a mean of 28 g of alcohol per day (the equivalent of 2 standard drinks per NIAAA definition) in the past month [28]. Excessive alcohol consumption is widespread in Russia and is closely linked with excess mortality particularly among Russian men [29], but also among PWID [30]. We assume that even in an environment where drinking is normative, excessive alcohol use might be associated with self-stigma [31], especially when alcohol consumption is disorderly and apparent to others, such as among people with more severe alcohol use disorders [32].…”
Section: Introductionmentioning
confidence: 99%